2006
DOI: 10.1007/s10545-006-0403-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Portuguese patients with mucopolysaccharidosis type II shows evidence that the IDS gene is prone to splicing mutations

Abstract: Mucopolysaccharidosis type II (MPS II) is an X-linked recessive lysosomal storage disease caused by a defect in the iduronate-2-sulfatase gene (IDS). Alternative splicing of the IDS gene can occur and the underlying regulatory mechanism may be rather complex. Nevertheless, little information is available on the role of variations at the IDS locus in the splicing process. Here we report that splice mutations at the IDS locus are an important source of MPS II pathogenicity, accounting for almost 56% of Portugues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 25 publications
7
39
3
1
Order By: Relevance
“…1C). This pattern of alternative transcripts is similar to that seen for the c.418+1G>C (Lualdi et al 2006) and c.418+1G>A (Alves et al 2006) mutations at the first nucleotide of intron 3, where four alternative transcripts were observed. Alves and colleagues (2006) also observed the cryptic exon 3a at low abundance in control transcripts.…”
Section: Splicing Aberrationssupporting
confidence: 82%
See 3 more Smart Citations
“…1C). This pattern of alternative transcripts is similar to that seen for the c.418+1G>C (Lualdi et al 2006) and c.418+1G>A (Alves et al 2006) mutations at the first nucleotide of intron 3, where four alternative transcripts were observed. Alves and colleagues (2006) also observed the cryptic exon 3a at low abundance in control transcripts.…”
Section: Splicing Aberrationssupporting
confidence: 82%
“…The cryptic exon generated in some transcripts in (C) is denoted 3a, as described by Alves and colleagues (2006). The Shapiro-Senapathy scores for the splice sites are shown in italic at the splice sites, as described by Lualdi and colleagues (2006) (Alves et al 2006;Vafiadaki et al 1998), it resulted in a transcript lacking the first 44 nucleotides of exon 3 (transcript 1) in addition to the correctly spliced transcript (transcript 2) for p.P86L (Fig. 1B).…”
Section: Splicing Aberrationsmentioning
confidence: 59%
See 2 more Smart Citations
“…The detection of this mutation is helpful for demonstrating that IDS gene has a high new mutation rate and remarkable hot spots (Rathmann et al, 1996). Recently, Alves et al(2006) confirmed that IDS gene has a high mutation rate of splicing site. The study of Lualdi et al(2006) revealed that point mutation of IDS gene can activate multiple larvaceous splicing sites, leading to mis-splicing RNA.…”
Section: Discussionmentioning
confidence: 91%